Optimalisasi Digital Marketing Airish Hotel Palembang Sebagai Srategi Kompetitif Industri Perhotelan Di Era Teknologi Informasi - Rifki Imayan; M. Miftah Farid (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Marketing strategies in the hospitality industry have changed significantly as a result of advances in information technology, particularly in terms of the use of digital marketing to increase competitiveness. As part of the hospitality industry, Airish Hotel Palembang must adapt to customer behavior that increasingly relies on digital media to obtain information and make accommodation decisions. The purpose of this study is to examine how Airish Hotel Palembang uses digital marketing optimization strategies to compete in the IT era. This research was conducted using a qualitative descriptive approach that employed observation, and documentation as data collection methods. The results showed that building the hotel's image, increasing brand visibility, and reaching a wider market were influenced by the use of informative and visual digital content, such as social media and the official website. However, there are still several issues that need to be addressed, such as limited content consistency and customer interaction management. Therefore, for Airish Hotel Palembang to remain competitive amid fierce competition in the hospitality industry in the IT era, digital marketing optimization must be carried out in a planned and sustainable manner.